Discovery of a small molecule targeting ULK1-modulated cell death of triple negative breast cancer in vitro and in vivo. Issue 4 (1st February 2017) - Zhang, Lan; Fu, Leilei; Zhang, Shouyue; Zhang, Jin; Zhao, Yuqian; Zheng, Yaxin; He, Gu; Yang, Shengyong; Ouyang, Liang; Liu, Bo
Abstract : ULK1 is identified as a target in TNBC; thus a small-molecule agonist is discovered by targeting ULK1-modulated cell death, associated with autophagy and apoptosis. Abstract : UNC-51-like kinase 1 (ULK1) is well-known to initiate autophagy, and the downregulation of ULK1 has been found in most breast cancer tissues. Thus, the activation of ULK1-modulated autophagy could be a promising strategy for breast cancer therapy. In this study, we found that ULK1 was remarkably downregulated in breast cancer tissue samples by The Cancer Genome Atlas (TCGA) analysis and tissue microarray (TMA) analysis, especially in triple negative breast cancer (TNBC). To design a ULK1 agonist, we integrated in silico screening and chemical synthesis to acquire a series of small molecule candidates. After rounds of kinase and anti-proliferative activity screening, we discovered the small molecule, LYN-1604, to be the best candidate for a ULK1 agonist. Additionally, we identified that three amino acid residues (LYS50, LEU53, and TYR89) were key to the activation site of LYN-1604 and ULK1 by site-directed mutagenesis and biochemical assays. Subsequently, we demonstrated that LYN-1604 could induce cell death, associated with autophagy by the ULK complex (ULK1-mATG13-FIP200-ATG101) in MDA-MB-231 cells. To further explore LYN-1604-induced autophagic mechanisms, we found some potential ULK1 interactors, such as ATF3, RAD21, and caspase3, by performing comparative microarray analysis. Intriguingly, we found that LYN-1604 induced cell death involved in ATF3, RAD21, and caspase3, accompanied by autophagy and apoptosis. Moreover, we demonstrated that LYN-1604 has potential for good therapeutic effects on TNBC by targeting ULK1-modulated cell death in vivo ; thus making this ULK1 agonist a novel potential small-molecule drug candidate for future TNBC therapy.